THE RELATIONSHIP BETWEEN COMPLIANCE WITH IRON TABLET CONSUMPTION AND NUTRITIONAL STATUS WITH ANEMIA AMONG PREGNANT WOMEN IN PUTRI AYU HEALTH CENTER, JAMBI CITY - Putri Lubis, Izmi Arisa; Basrowi, Ray Wagiu; Pratiwi, Dessy (Ridwan Institute, 2025)
Background: Anemia during pregnancy remains a significant public health concern in Indonesia, with a high prevalence and adverse outcomes for both mothers and infants. Iron supplementation and maternal nutritional status are key factors in preventing anemia. This study aimed to examine the association between compliance with iron tablet consumption and nutritional status (chronic energy deficiency) with the incidence of anemia among pregnant women. Methods: A cross-sectional study was conducted at Putri Ayu Health Center, Jambi City, involving 100 pregnant women selected using accidental sampling. Data on hemoglobin levels, upper arm circumference (MUAC), and iron tablet intake were collected through interviews and direct measurement. Anemia was defined as Hb <11 g/dL. Nutritional status was categorized based on MUAC <23.5 cm as chronic energy deficiency (CED). Data were analyzed using descriptive statistics and bivariate (Chi-square) analysis. Results: While statistical associations between CED and iron tablet compliance with anemia were not significant, higher proportions of anemia were observed among women with CED and those who consumed fewer than 30 tablets. Additionally, descriptive trends showed that women who began supplementation early in pregnancy—particularly in the first trimester—were less likely to develop anemia compared to those who initiated later. Conclusions: Although not statistically significant, the findings suggest that poor nutritional status and low adherence to iron tablet supplementation may increase the likelihood of anemia in pregnancy. Early and consistent supplementation, particularly from the first trimester, should be emphasized in antenatal care programs to prevent iron deficiency-related complications.